(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
Language may be considered as a subject for interdisciplinary study, constructed through dialog across many areas, including the Philosophy of Language and Psychology. With this in mind, this work sought to analyze the reconciliation between the propositions of Bakhtin and Skinner. The most important point analyzed is the notion of language as the product of interactions between socially organized individuals. Bakhtin focuses on the verbal interaction between speakers, while Skinner focuses on the doing, of necessity mediational, of the subject acting verbally. Both authors point to the importance of social determinants in verbal action and they are in agreement when criticizing the notion of language as a reflection of the internal condition of the speaker. Nevertheless, there are divergent elements as well as points of convergence. From the results of this research, we may ascertain that this kind of work, of reconciling areas and theories, does not aim to replace one area with the other, but in fact aims to open up new possibilities of study.